Case Report: Neuroblastoma Breakpoint Family Genes Associate With 1q21 Copy Number Variation Disorders - Zhu, Lijuan; Su, Xiaoji (Frontiers in Genetics, 2021)
Microduplications and reciprocal microdeletions of chromosome 1q21.1 and/or 1q21.2 have been linked to variable clinical features, but the underlying pathogenic gene(s) remain unclear. Here we report that distinct microduplications were detected on chromosome 1q21.2 (GRCh37/hg19) in a mother (255 kb in size) and her newborn daughter (443 kb in size), while the same paternal locus was wild-type. Although the two microduplications largely overlap in genomic sequence (183 kb overlapping), the mother showed no clinical phenotype while the daughter presented with several features that are commonly observed on 1q21 microduplication or microdeletion patients, including developmental delay, craniofacial dysmorphism, congenital heart disease and sensorineural hearing loss. NBPF15 and NBPF16, two involved genes that are exclusively duplicated in the proband, may be the cause of the clinical manifestations. This study supports an association between NBPF genes and 1q21 copy number variation disorders.